Pharmacokinetics, safety, tolerability and immunogenicity of FKB327, a new biosimilar medicine of adalimumab/Humira, in healthy subjects. (9th March 2017) - Puri, Adeep; Niewiarowski, Andrew; Arai, Yasumasa; Nomura, Hideaki; Baird, Mark; Dalrymple, Isobel; Warrington, Steve; Boyce, Malcolm
Abstract : Aims: To compare the pharmacokinetics, safety, tolerability and immunogenicity of FKB327, a biosimilar of adalimumab, with European Union (EU)‐approved Humira and US‐licensed Humira after single subcutaneous doses in healthy subjects. Methods: In a randomized, double‐blind, parallel‐group study, 180 healthy subjects received by subcutaneous injection 40 mg of EU‐Humira, or US‐Humira, or FKB327, in a 1:1:1 ratio, stratified by bodyweight. Pharmacokinetics, local tolerability, immunogenicity, adverse events, vital signs, electrocardiography and laboratory safety tests were assessed prior to and up to 1536 h after treatment. Results: The pharmacokinetics of FKB327 were similar to those of both EU‐ and US‐Humira. The 90% confidence interval for the ratios of AUC0–t, AUC0–inf, and Cmax geometric means were in the acceptance range for bioequivalence of 0.80–1.25 for all three pairwise comparisons by analysis of covariance with baseline characteristics age, body weight and (for Cmax only) sex as covariates. Tolerability of all three treatments was equally acceptable, and there were no differences in safety profile or immunogenicity among the three treatments. Overall, antidrug antibodies were detected in approximately 70% of subjects who received each treatment; higher titres were associated with faster elimination of adalimumab. Conclusions: The study demonstrated pharmacokinetic similarity of FKB327 with EU‐ and US‐Humira. FKB327 was well tolerated by healthy subjects, with adverse effects similar to Humira. If clinical similarity to Humira, including efficacy, can be shown in patients, FKB327 will meet the criteria for biosimilarity to Humira.